Effect of Substituents on Partial Photocatalytic Oxidation of Aromatic Alcohols Assisted by Polymeric C3N4. Issue 11 (16th May 2019) - Krivtsov, Igor; Ilkaeva, Marina; García‐López, Elisa I.; Marcì, Giuseppe; Palmisano, Leonardo; Bartashevich, Ekaterina; Grigoreva, Ekaterina; Matveeva, Ksenia; Díaz, Eva; Ordóñez, Salvador
Abstract: In the present work we scrutinize the effect of substituents in the phenyl ring of the benzyl alcohol on its photo‐oxidation to the corresponding benzaldehyde driven by polymeric carbon nitride photocatalyst in aqueous medium. It has been established that electron donating (ED) substituents in para‐ and ortho‐ position with respect to the CH2 OH‐group promote the reactivity of the substrate without compromising the selectivity towards benzaldehyde formation, maintaining it in the range of 84–98 %, if compared to the unsubstituted molecule. The same observation is true for meta‐ substituted benzyl alcohol with an electron withdrawing (EW) group. On the other hand, the presence of ED‐group in meta‐ position or EW‐group in para‐ position with respect to the CH2 OH‐group reduces the reactivity as well as the selectivity towards the aldehyde production, resulting in the values of selectivity ranging from 40 to 80 %. Quantum chemical calculations have allowed to establish that the reactivity correlates with the positive charge on the benzylic carbon in benzyl alcohol cation intermediate, while the selectivity, most probably, is conditioned by a negative charge on the carbon atoms in the phenyl ring being a target for an electrophile attack. The modification of the polymeric C3 N4 photocatalyst with H2 O2 reduces the unselective benzyl alcohol oxidation, thus favouring the higher selectivity towards benzaldehyde production. Abstract : Photocatalysis : The respective position of substituents in phenyl ring of benzyl alcohols determines the selectivity of their carbon nitride‐driven photo‐oxidation to benzaldehydes. A negative charge on the phenyl ring of benzyl alcohols induced by substituents triggers a ring opening reaction, thus reducing the selectivity towards benzaldehyde formation. This reaction can be avoided by blocking amine‐terminated sites of polymeric carbon nitride with H2 O2 .